Monitoring and Controlling Ground D Toilet Area Lighting at Bedengan Tourism Park Malang Using Wireless Sensor Network - Soelistianto, Farida Arinie; Firdaus, Achmad Faisal; Novianti, Atik (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
Electric lighting in Taman Wisata Bedengan Malang has a crucial role in supporting visitor comfort, especially at night. To overcome this problem, this research proposes a monitoring and management system for power, voltage, and security of public street lighting equipment based on wireless sensor network (WSN) with additional energy support from solar panels. The purpose of this research is to design and implement a WSN-based street lighting system, where the lights will dim automatically when no one passes by and turn on fully when someone passes by. This system uses ESP32 components, Arduino LGT8F328P, LoRa module type E220-900T22D, PIR sensor, PZEM 004-T, AC Dimmer, and Real Time Clock (RTC). The research aims to design and make WSN-based public street lighting where the lights will dim if no one passes by, and will turn on 100% when someone passes by. This research uses ESP32, Arduino LGT8F328P, LoRa module type E220-900T22D, PIR, PZEM, AC Dimmer, and Real Time Clock. The results show that the PZEM sensor has a reading accuracy of 99.995%. The maximum distance of data transmission by the LoRa module reaches 160 meters. Charging by the solar panel for 6 hours is able to reach the full capacity of the battery of 100 Ah, with a battery life of 386 hours (discharge of 0.2588 Ah). System throughput was recorded at 825 Kb/s, with packet loss of 0.996% and average delay of 0.585 seconds. The measurement difference between the PZEM sensor and the avometer is 0.995%. In addition, testing the system through the website using the QoS method resulted in a throughput of 82.5%, packet loss of 0.996%, and average delay of 0.585 seconds. The lighting system can operate in two modes, namely manual and automatic modes.